Neuromodulation 3.0: brain-apparatus communication-based neuromodulation - Dezhong Yao (Brain-Apparatus Communication)
Background Neuromodulation is a rapidly developing field, with various new technologies for the treatment of various neurological and neuropsychiatric disorders, but it still suffers from a few big challenges such as the individual differences and effectiveness predictability. Therefore, it is an important issue to clarify the development routine of neuromodulation technology (NMT) to address these difficulties.Proposal Based on the relation between NMT and subject, we suppose to divide NMT into three generations: (1) open-loop NMT where neuromodulation and subject are independent; (2) one closed-loop such as bidirectional brain–computer interface (BCI) based NMT where neuromodulation is brain state dependent; and (3) Multiple closed-loops such as using brain-physical instrument loop and brain-living organ loop simultaneously, that is, brain-apparatus communication (BAC)-based NMT where neuromodulation is dependent on both brain and body status.Prospect The effectiveness of NMT3.0 based on the combinations of various BACs would be of much higher sustainability, because it modulates the brain and the peripheral system simultaneously, thus it has chance to move the man systematically to a new state.